An investigation into the crystalline morphology transitions in poly-L-lactic acid (PLLA) under uniaxial deformation in the quasi-solid-state regime. (April 2018) - Billimoria, Kharmen; Heeley, Ellen L.; Parsons, Nathan; Figiel, Łukasz
Graphical abstract: Highlights: The mechanical behaviour of poly-l -lactic acid depends strongly on T d . SAXS/WAXS data showed that strain-induced crystallization occurs on drawing. The disordered α′ crystal form was observed post-draw at T d between 60 and 80 °C. Drawing at T d  ≥ 90 °C, resulted in the ordered α crystal form directly. An oriented lamellar macromorphology developed post-draw, in samples on annealing. Abstract: The mechanical behaviour, crystalline and macromorphology structure development during uniaxial deformation and annealing of poly-l -lactic acid (PLLA), with varying strain rate and draw temperatures ( T d ) above T g, have been investigated using small- and wide-angle X-ray scattering (SAXS/WAXS), microscopy, thermal and mechanical techniques. The mechanical behaviour of PLLA, was strongly dependent on T d where embrittlement and eventual failure were observed as T d was increased, during uniaxial drawing of the amorphous polymer. This was mirrored in the bulk surface morphology where crazing, microvoiding and cavitation occurred with increasing T d . SAXS/WAXS data showed that strain-induced crystallization occurs on drawing, but crystallite orientation decreased with increasing T d, due to chain relaxation at temperatures ≥30 °C above T g . However, no long-range oriented lamellar macromorphology was observed post-draw directly and only developed in the samples that were step annealed at temperatures above T d . Also, the disordered α′ crystal form was observed post-draw at T d between 60 and 80 °C, whereas T d  ≥ 90 °C, resulted in the ordered α crystal form directly. However, on annealing at temperatures of ≥110 °C, the α′-α crystal transition ensued and in all samples, an oriented lamellar macromorphology developed. Therefore, T d and post-draw annealing, have a significant influence on the mechanical properties, crystallinity and crystalline phase transformation in PLLA, which in-turn, affects the polymers medical and industrial applications.